Evaluation of maize hybrids resistance to northern corn leaf blight in Karo Highland. Issue 1 (March 2021) - Permana, A; Hanafiah, D S; Hasanuddin,
Abstract: Around two-thirds of corn area in North Sumatera are in high altitude places, where northern corn leaf blight limits yield. Evaluation was performed to 125 new hybrids for their resistance to northern corn leaf blight and yield components in Garingging, District of Karo, North Sumatera, from October 2019 to March 2020. Experiments were arranged in Augmented RCBD with 4 checks, Artificial inoculation was applied to ensure high and uniform disease pressure. Eight new hybrids exceeded at least 3 checks regarding to disease resistance and ear weight, namely N399, G163, N396, N374, D651, N020, D635, and N031. Hybrid N399 has ear weight above 4 checks and G163 has better AUDPC than the 4 checks, suggesting promising hybrids for developing varieties in areas with NCLB pressure. Significant association with AUDPC was seen in incubation period, ear diameter, ear length, and ear weight. High GCV was observed in disease resistance traits, while high heritability is estimated in incubation period, AUDPC, ear diameter, and ear length. Incubation period may be used in early selection.